Magnetic Skin for Voice Disorders with Real‐Time Lip Translation - Montserrat Ramirez‐De Angel; Alexander Przybysz; Eckaard le Roux; Nora Alamoudi; Li Zhang; Saptami Suresh Shetty; Khaled N. Salama (Advanced Intelligent Systems)
The next generation of wearable technology is embodied by flexible, biocompatible magneto‐skin that seamlessly integrates with the body, offering tunable permanent magnetic properties to any surface it adheres to. When combined with magnetic sensors, this innovative material transforms into a wearable magnetic system. Drawing inspiration from the adhesion mechanics of octopus suckers, an adhesive magnetic skin designed for speech therapy applications is introduced. This skin‐attachable patch adheres securely to both dry and wet skin without causing irritation, providing comfort during extended wear. The system, comprising two small patches attached to the lower lip, a wireless headset with embedded magnetic field sensors, and a mobile application powered by a convolutional neural network, translates lip movements into spoken words. The system predicts successfully 92.54% of the cases with non‐seen data and 90.21% of the real‐time cases. With customizable patch size and an intuitive user interface, this edge‐based device offers a groundbreaking solution for individuals with voice disorders, providing a tailored, non‐invasive therapeutic approach that adapts to the unique needs of users and therapists alike.